Friday

August 29, 2014

August 29, 2014

Posted by **Blue** on Thursday, September 29, 2011 at 7:38pm.

Write in terms of ln(x), ln(x+1), and ln(x+2)

is the correct steps this?

lnx^2 + ln(x+1) - ln(x+2) = 2lnx + ln(x+1) - ln(x+2)

- Math -
**Steve**, Friday, September 30, 2011 at 5:17amGood job.

**Related Questions**

calculus - 1. e^ln3 - 2lnx 2. 2(lnx)^2 + lnx - 1 =0 3. d/dx (e^x . e^e^x)

calculus - The volume of a solid is given by V=pi x^2(lnx)^2. what is the ...

Calculus - Solve for x: lnx^3 - 2lnx = 1 Please try and show how you got the ...

L'Hopital's rule - Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work...

calculus - sorry to ask a second question so soon, but i'm just not getting this...

Calculus 1 - Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36...

College Calc - Problem: y=sqrtx ^1/x. Find DY/DX. ln(f(x))=lnx^1/2x or lnx to ...

Calculus - dy/dx= (y^2 -1)/x 1. Give the general equation of the curves that ...

calc - integral of 1 to e^4 dx/x(1+lnx) 1+lnx = a => dx/x = da dx/ x(1+lnx...

math - how would you solve for y in this problem: ln(y-1)-ln2 = x +lnx ln(y-1)-...